Different organic manure sources and NPK fertilizer on soil chemical properties, growth, yield and quality of okra - Adekiya, Aruna Olasekan (Sci Rep, 2020)
Use of organic manures to meet the nutrient requirement of crop would be an inevitable practice in the years to come for sustainable agriculture since organic manures generally improve the soil physical, chemical and biological properties. Hence, field experiments were carried out in 2017 and 2018 to compare the impact of different organic manures and NPK fertilizer on soil properties, growth, yield, proximate and mineral contents of okra (Abelmoschus esculentus L.). The treatments each year 2017 and 2018 consisted of: rabbit manure, cow dung, poultry manure, green manure [Mexican sunflower (Tithonia diversifolia Asteraceae)], pig manure, NPK 15-15-15 fertilizer applied at 120 kg N ha(−1) and a control (no manure/inorganic fertilizer). The seven treatments were laid out in a randomized complete block design with three replication. Organic manures and NPK fertilizer increased the soil organic matter (OM), N, P, K, Ca and Mg (NPK fertilizer did not increase OM, Ca and Mg significantly), growth, yield, minerals, protein, ash, carbohydrate and mucilage contents of okra fruit as compared with control. Organic manures improved okra yield compared with NPK fertilizer. Okra growth and yield parameters were significantly higher in 2018 compared with 2017. Control, rabbit manure, cow dung, poultry manure, green manure, pig manure and NPK fertilizer in 2018 increased the pod yield of okra by 9.7%, 35.3%, 57.9%, 36.2%, 39.2%, 45.5% and 3.2%, respectively compare with the same treatment in 2017. Amongst various organic manures, poultry manure produced significantly higher plant growth, yield, mineral and proximate composition of okra because of its high soil chemical properties which could be related to its lowest C: N ratio, lignin and lignin: N ratio. Results also showed that okra grown during high intensity rainfall has higher yield but with reduced quality except its mucilage content. Therefore, planting of okra with poultry manure under moderate rainfall will enhance the health benefit from the fruit, however, those that desire its mucilage content planting during high rainfall is recommended.